Criminal minds. The first season [videorecording (DVD)] - Patinkin, Mandy; Gibson, Thomas, 1962-; Glaudini, Lola, 1972-; Moore, Shemar, 1970-; Gubler, Matthew Gray, 1980-; Cook, A. J., 1978- (CBS DVD., 2006)
Join an elite team of FBI profilers as they analyze the country's most twisted criminal minds, anticipating their next moves before they can strike again.